Soil Organic Carbon and Nitrogen Feedbacks on Crop Yields under Climate Change. Issue 1 (1st August 2018) - Basso, B.; Dumont, B.; Maestrini, B.; Shcherbak, I.; Robertson, G. P.; Porter, J. R.; Smith, P.; Paustian, K.; Grace, P. R.; Asseng, S.; Bassu, S.; Biernath, C.; et al.
Abstract : Core Ideas: SOC decline, due to increased temperatures, reduces wheat and maize yields globally. CO2 increase to 540 ppm partially compensates yield losses due to increased temperatures. Accounting for soil feedbacks is critical when evaluating climate change impacts on crop yield. A critical omission from climate change impact studies on crop yield is the interaction between soil organic carbon (SOC), nitrogen (N) availability, and carbon dioxide (CO2 ). We used a multimodel ensemble to predict the effects of SOC and N under different scenarios of temperatures and CO2 concentrations on maize ( Zea mays L.) and wheat ( Triticum aestivum L.) yield in eight sites across the world. We found that including feedbacks from SOC and N losses due to increased temperatures would reduce yields by 13% in wheat and 19% in maize for a 3°C rise temperature with no adaptation practices. These losses correspond to an additional 4.5% (+3°C) when compared to crop yield reductions attributed to temperature increase alone. Future CO2 increase to 540 ppm would partially compensate losses by 80% for both maize and wheat at +3°C, and by 35% for wheat and 20% for maize at +6°C, relative to the baseline CO2 scenario.